2020
DOI: 10.1002/per.2309
|View full text |Cite
|
Sign up to set email alerts
|

How Are Personality States Associated with Smartphone Data?

Abstract: Smartphones promise great potential for personality science to study people's everyday life behaviours. Even though personality psychologists have become increasingly interested in the study of personality states, associations between smartphone data and personality states have not yet been investigated. This study provides a first step towards understanding how smartphones may be used for behavioural assessment of personality states. We explored the relationships between Big Five personality states and data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 118 publications
(294 reference statements)
3
21
0
Order By: Relevance
“…Future personality change intervention studies should take the effects of demand characteristics systematically into account and should include measures of actual behaviors (e.g., savings or work attendance) to address these biases. Also, future research is needed to investigate whether self-and observer-reported changes are reflected in behavioral indicators captured by smartphone data (55). Second, the entire intervention was delivered via the PEACH smartphone application without any personal contact with participants.…”
Section: Discussionmentioning
confidence: 99%
“…Future personality change intervention studies should take the effects of demand characteristics systematically into account and should include measures of actual behaviors (e.g., savings or work attendance) to address these biases. Also, future research is needed to investigate whether self-and observer-reported changes are reflected in behavioral indicators captured by smartphone data (55). Second, the entire intervention was delivered via the PEACH smartphone application without any personal contact with participants.…”
Section: Discussionmentioning
confidence: 99%
“…Future personality change intervention studies should take the effects of demand characteristics systematically into account and should include measures of actual behaviors (e.g., savings or work attendance) to address these biases. Also, future studies should investigate whether self-and observer-reported changes are reflected in behavioral indicators captured by smartphone data (55). Second, the entire intervention was delivered via the PEACH smartphone application without any personal contact with participants.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, past work on the prediction of personality traits from smartphone data suggests that individual levels of personality traits can be predicted from sensing data above chance for most traits (e.g., Stachl, Au, et al, 2020). Some initial studies have also begun to examine the prediction of personality states from sensing data, suggesting pre dictability for Extraversion states only (Rüegger et al, 2020). Cumulatively, personality sensing research provides new insights into people's characteristic behavioral patterns (e.g., stable tendencies, dynamic variability) and new opportunities for automating per sonality assessment (e.g., self-reported or observed behavioral dimensions; Harari et al, 2020).…”
Section: Mobile Sensingmentioning
confidence: 99%